Digital Religious Services: Analysis of Religious Fusion and Entertainment in the Short Film Cerita Hijrahku - Al Jufri, Muhammad Arman; Ar, Muhammad Syafi’i As’ad (The Sunan Ampel Review of Political and Social Sciences, 2022)
This article discusses the presence of new religious digital services reflected in the Muslim inspiration film "Cerita Hijrahku". Through new media platforms such as Youtube, this film is here to fulfill the religious learning desires of young Muslims who have connected, confident, and creative characters. This is a new phenomenon in the millennial era and at the same time confirms that religious learning is no longer just about attending religious events, but also through various ways. The two points outlined include: first, how digital religious services form in the millennial era; and second, how to mean the film "Hijrahku Story" in representing Islam in new media as one of the loci of religious learning. This research is qualitative using Julia Kristeva's inter-technicality approach. As a result, first, digital services are incarnated in two forms, namely da'wahtainment and religiotainment. Da'wahtainment refers to the combination of da'wah (read: lectures) with entertainment, while religiotainment is a combination of religion and entertainment. However, the scope of religiotainment is wider than da'wahtainment, covering movies, fashion, music, and social media content, including memes. Second, despite having different meanings, the signs presented in the short film "Cerita Hijrahku" boil down to the message of the conception of hijrah to become a good Islamic person following the standard religious text. The meaning presented by the audience, confirms that the short film "Cerita Hijrahku" is one of the digital religious services for young Muslims.